Effect of Vitamin-D Supplementation in Children with Moderate-Severe Persistent Allergic Rhinitis - Akram, Sumera (International Journal of Pathology, 2021)
Objective; To compare serum vitamin D level in pediatric cases of persistent moderate-severe allergic rhinitis with healthy children and to assess efficacy of vitamin D supplementation on treatment of allergic rhinitis in these cases.Study design, place & duration; Nonrandomized controlled trials. The study was carried out from September 2019 to September 2020 in Combined Military Hospital Mardan and Mardan Medical Complex.Methodology; One hundred and twenty pediatric cases (5 -15 years) of moderate-severe persistent allergic rhinitis were selected from outpatient department and their serum 25 (OH)D levels were compared with 120 healthy children of same age. The allergic rhinitis children (120) were divided in two groups of 60 each, Group A and Group B. The symptoms of cases were assessed and recorded. Rhinorrhea was assigned score from 0 to 3, 0 for no rhinorrhea, 1 for mild, 2 for moderate and 3 for severe rhinorrhea. Similarly other symptoms of itching, sneezing, nasal obstruction and nasal rubbing were assigned scores and recorded. Group A cases were given daily vitamin D (800IU) in addition to oral antihistamine (loratidine), intranasal corticosteroids (Budesonide), oral leukotriene inhibitors (Montelukast) and intranasal xylometasoline (Xynosine nasal drops). Group B children were given above mentioned medicines only. After four weeks they were assessed in terms of improvements of symptoms and compared. All data was analyzed with help of SPSS 21.Results; Among allergic rhinitis children, there were 64 (53.3%) males and 56 (46.7%) females. Mean age of children was 9.90 +3.06 years. Out of them, 51 (42.5%) were Vitamin D deficient, 46 (38.3%) were Vitamin D insufficient and 23 (19.2%) had sufficient serum Vitamin D levels. Total 80.8% children with allergic rhinitis had low serum vitamin D levels. Among 120 healthy children, there were 61 males (50.8%) and 59 females (49.2%) with mean age 10.41 + 3.07 years. In healthy children, there were 30.8% cases of vitamin D deficiency and 32.5% cases of vitamin D insufficiency (total 63.3% cases of low serum vitamin D) and 36.7% children had normal serum vitamin D. In contrast 19.2% allergic rhinitis children had normal serum vitamin D levels.Group A children receiving additional daily Vitamin D (800IU) had significantly better improvement in symptoms of allergic rhinitis (rhinorrhea, nasal itching, sneezing, nasal obstruction) as compared to the group only receiving allergic rhinitis treatment (Group B). Symptom of nasal rubbing also got alleviated after 04 weeks but the improvement was insignificant (p=0.092).Conclusion; Children with persistent moderate-severe allergic rhinitis had significantly lower serum levels of serum vitamin D as compared to healthy children of same age and daily supplementation of vitamin d (800IU) helps alleviating the symptoms of allergic rhinitis in addition to standard therapy of allergic rhinitis.